EVALUASI KINERJA TEKNOLOGI INFORMASI BERDASARKAN DOMAIN MONITOR AND EVALUATE MENGGUNAKAN COBIT 4.1 (STUDI KASUS: PT. GLOBAL INFOTECH SOLUTION) - Anni Sri Rahayu; Agustinus Fritz Wijaya (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2020)
PT Global Infotech Solution is a service, marketing and IT consulting company, among others, data solutions, security systems, cloud and managed services. In carrying out business processes there are several factors that must be considered by the company, not only focusing on the use of information technology that supports business processes, but the company must be able to focus on maintaining, monitoring, managing and ensuring that the company complies with applicable laws and regulations so that the company is able provide publishers with business objectives. Therefore, researchers use the Monitor and Evaluate domain. The purpose of this study is to measure the level of maturity of a company's information technology based on the process of maintenance, management and the extent to which companies obey the applicable laws and regulations. The research methodology is a qualitative method, with data collection through observation and interviews with informants. The results of this study are the level of maturity the company and provide advice to companies so that the application of information technology can be better, effective and efficient.